Let S be the infinite sum given by S = n = 0 ∑ ∞ 1 0 2 n a n where ⟨ a n ⟩ n ≥ 0 is a sequence defined by a 0 = a 1 = 1 and a j = 2 0 a j − 1 − 1 0 8 a j − 2 for j ≥ 2 . If S can be expressed in the form of b a , where a and b are coprime positive integers, then what is a ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
FYI: the denominator of the parenthetical quantities in your second line should be 1 0 0 instead of 1 0 .
First we show that the sum converges, using the following lemma:
Lemma: ∣ a n ∣ ≤ 5 0 n for all n .
Proof: By induction. It's true for n = 0 , 1 , and then supposing it's true for 0 , 1 , … , k − 1 , we have ∣ a k ∣ ≤ 2 0 ∣ a k − 1 ∣ + 1 0 8 ∣ a k − 2 ∣ ≤ 2 0 ⋅ 5 0 k − 1 + 1 0 8 ⋅ 5 0 k − 2 = 5 0 k ( 5 2 + 2 5 0 0 1 0 8 ) < 5 0 k .
So the sum converges because the absolute value of the n th term is ≤ ( 1 / 2 ) n .
To evaluate the sum, write n = 2 ∑ ∞ 1 0 2 n a n − 2 0 a n − 1 + 1 0 8 a n − 2 n = 2 ∑ ∞ 1 0 2 n a n − 2 0 n = 2 ∑ ∞ 1 0 2 n a n − 1 + 1 0 8 n = 2 ∑ ∞ 1 0 2 n a n − 2 ( S − 1 − 1 0 0 1 ) − 5 1 n = 2 ∑ ∞ 1 0 2 ( n − 1 ) a n − 1 + 1 0 0 0 0 1 0 8 n = 2 ∑ ∞ 1 0 2 ( n − 2 ) a n − 2 ( S − 1 − 1 0 0 1 ) − 5 1 ( S − 1 ) + 1 0 0 0 0 1 0 8 S S ( 1 − 5 1 + 1 0 0 0 0 1 0 8 ) S = 0 = 0 = 0 = 0 = 1 − 5 1 + 1 0 0 1 = 1 0 0 0 0 − 2 0 0 0 + 1 0 8 1 0 0 0 0 − 2 0 0 0 + 1 0 0 = 2 0 2 7 2 0 2 5 , so a = 2 0 2 5 .
Oh wow, I'm not familiar with this technique of finding the sum. Thanks! +1
Just curious, why do we have to prove that the sum converges? I feel like your first half of the solution is not necessary. I mean, if we have found the sum to be finite, doesn't it automatically implies that the sum converges? Or is there a case where the sum converges "through other means" and we just want to make sure it converges "conventionally"?
EDIT: Oh wait, nevermind. I got it. You have defined the sum to be S in your latter part of your solution. To do so, we need to prove that S is finite first. Otherwise, there might be a case of ∞ − ∞ .
I shall right an easy explanation. Say, (a j)/10^2j=P j. So, S=P 1+P 2+..... Now ,you easily can find the following relation P j=0.2P j-1-0.0108P j-2 ,P j-1=0.2P j-2 -0.0108P j-3... ... ,... ,P 2=0.2P 1 - 0.0108P 0 Now add L.H.S and R.H.S. P 2+P 3+...=0.1892(P 1+P 2+...) -0.0108. Add P 1+P_0 to both sides. Then it becomes S=0.1892(S-1)+1.01-0.0108 S=0.1892S+0.81 S=2025/2027. So, a=2025
Problem Loading...
Note Loading...
Set Loading...
Solving the recurrence relation, we obtain a n = 4 2 2 2 + 9 i ( 1 0 + 2 i 2 ) n + 4 2 2 2 − 9 i ( 1 0 − 2 i 2 ) n for all n , and so the sum is n = 0 ∑ ∞ 1 0 2 n a n = 4 2 2 2 + 9 i n = 0 ∑ ∞ ( 1 0 0 1 0 + 2 i 2 ) n + 4 2 2 2 − 9 i n = 0 ∑ ∞ ( 1 0 0 1 0 − 2 i 2 ) n = 4 2 2 2 + 9 i × 1 − 1 0 0 1 0 + 2 i 2 1 + 4 2 2 2 − 9 i × 1 − 1 0 0 1 0 − 2 i 2 1 = 2 0 2 7 2 0 2 5 making the answer 2 0 2 5 .